Persiapan Menuju Badan Layanan Umum Daerah (BLUD) Penuh Studi Pada Tiga Puskesmas Di Pemerintah Daerah Kabupaten Magelang - Rina Susanti Nasution (Master in Accounting Program, 2015)
Regional Public Service Agency (RPSA) is one of government efforts to improve the quality of community health service. The gradual status of RPSA obtained by community health centers in Magelang District since January 2015 applies only three years maximum in accordance with Government Regulation Number 23 Year 2005. Therefore, community health service in Magelang District should start preparing themselves to improve their status into full RPSA. This purpose of this study was to analyze the preparation in three community health centers towards full RSPA in Magelang District Government. Full RSPA status are obtained by meeting the requirements of substantive, technical and document administrative score of community health service between 80-100. The analysis was conducted by evaluating the initial document of RPSA and intervews based on the perspective of Actor-Network Theory (ANT) to further analyze what preparation performed by community health centers especially the head of community health center as the manager of the health center. In the perspective on ANT, we follow the actors to learf from the actors themselves, not only on what they do but how and why they do it. The result of the study showed that the role of head of community service is very important as actant in achieving the interest towards full RPSA by establishing team of document drafting of RSPA requirements, provide motivation and commitment in the internal of community health center. However, as actant, head of community health center also needs other actors such as in the internal of community health center, Department of Health, assessment team/local government and team of accounting experts of UGM. Problems encountered in the preparation are, incriminating indicators of administrative documents, limited Human Resources (HR), and the role of actors outside the community health center has not fully provide support for community health centers.